Structure and function of extracellular O-GlcNAc. (June 2019) - Ogawa, Mitsutaka; Okajima, Tetsuya
Abstract : Extracellular O -GlcNAc is a unique modification restricted to the epidermal growth factor (EGF) domain-containing glycoproteins. This O -GlcNAcylation is catalyzed by the EGF-domain specific O -GlcNAc transferase (EOGT), which is localized in the lumen of endoplasmic reticulum. In humans, EOGT is one of the causative genes of a congenital disease, Adams–Oliver syndrome. EOGT is highly expressed in endothelial cells and regulates vascular development and integrity by potentiating Delta-like ligand-mediated Notch signaling. In Drosophila, Eogt modifies Dumpy, an apical extracellular matrix glycoprotein, and affects Dumpy-dependent cell-matrix interaction. In this review, we summarize the current findings of the structure and functions of extracellular O -GlcNAc in animals.